From Individual Eudaimonia to Social Flourishing. Perspectives On Happiness in the Work of Martha Nussbaum - Ferreira, Marco; Faustino, Marta (Revista Archai, 2026)
Martha Nussbaum is one of the main references for the contemporary debate on human happiness and well-being. Her main contributions are, on the one hand, her study and analysis of ancient philosophy as a therapy of the soul, and, on the other hand, the capabilities approach, which she developed with Amartya Sen, as an ideal for the organization of society, in order to provide human beings with full development and flourishing. Although closely related in their practical and transformative purpose, these two visions of human happiness and the means to achieve it diverge radically and can even be considered contradictory. If for the Hellenistic schools eudaimonia is an individual task, alien to and independent of any social or collective flourishing, for the capabilities approach, social or collective flourishing is the true condition of possibility for any individual flourishing. In this essay we will discuss both approaches and try to show how they are not only reconcilable but even closely related in Nussbaum’s thought, constituting two different but complementary approaches to the problem of human flourishing and the philosophical pursuit of happiness.